DEVELOPING AUTOPLAY BASED READING MATERIALS FOR SENIOR HIGH SCHOOL STUDENTS - Hendi hidayat; Tohidin Tohidin; Sumadi Sumadi (IAIN Syekh Nurjati Cirebon, 2021)
This study was intended to develop autoplay-based Reading learning media that meet the valid, practical, and effective criteria. The method used in this research is research and development method with ADDIE development design (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques in this study used questionnaires and tests. Based on the results of the research that has been described, it can be concluded that the autoplay-based reading learning media developed has met the valid criteria, because the average expert validation results are 90.67 (valid) including good criteria. In addition, autoplay-based reading learning media also meets practical criteria, because student responses to the use of autoplay-based reading learning media are 85%. The score is included in the good category, namely the practical autoplay-based reading learning media used in the learning process. Autoplay-based reading learning media also meets the effective criteria, because the average value of student learning outcomes is 87. This value exceeds the KKN set by the school, which is 75.